Extensive impact of COVID‐19 pandemic on pelvic floor dysfunctions care: A nationwide interdisciplinary survey. Issue 2 (25th January 2021) - Sacco, Emilio; Gandi, Carlo; Li Marzi, Vincenzo; Lamberti, Gianfranco; Serati, Maurizio; Agro', Enrico Finazzi; Soligo, Marco; ,
Abstract: Aims: To investigate the impact of COVID‐19 pandemic on health‐care provision to patients suffering from pelvic floor dysfunctions in Italy. Methods: A retrospective web‐based interdisciplinary survey was mailed by the Italian Society of Urodynamics to members involved in pelvic floor dysfunctions management from June 22, 2020 to July 17, 2020. The 84‐item questionnaire investigated the period March–June 2020 (first epidemic wave) and showed high content validity. The primary outcome was the mean rate of cancellation for health‐care services. Secondary outcomes included estimation of the accumulated surgeries backload until return to baseline activity and of the recovery pattern, using linear regression and scenario‐based forecasting. Results: A total of 85 participants provided complete responses. Respondents were mostly urologists (47%), followed by gynecologists (29.5%) and physiatrists (17.6%). On average, 78.4% of outpatient services and 82.7% of functional surgeries were canceled, without significant differences by geographical distribution. An impact on patients' quality of life was anticipated by most of the respondents (87%) and 48.2% also reported potentially serious health risks for patients. Thirty‐three percent of the respondents reported the use of telemedicine. If the nation‐wide surgical activity increases by 20% postpandemic, it would take 37 months to clear the backlog of functional surgeries. We acknowledge the inherent limitations of the survey methodology and retrospective design. Conclusions: Access to care for patients suffering from pelvic floor dysfunctions has been dramatically affected by the COVID‐19 outbreak. The indirect effects of this unprecedented disruption on pelvic floor dysfunctions care may last for several months.